Tropical Modernism/Environmental Nationalism: The Politics of Built Space in Postcolonial Sri Lanka. Issue 2 (4th May 2017) - Jazeel, Tariq
Abstract: This paper explores the relationships between Sri Lanka's tropical architecture, its negotiation of the Sri Lankan environment, and the post-colony's contested politics of nationhood. By focussing on the work of Minnette de Silva, an early pioneer of Sri Lankan tropical architecture, and on the stylistic and aesthetic influences on her work, and hence on contemporary manifestations of the genre, the paper traces the connections between a conscious desire amongst tropical modernists to build with Sri Lanka's superabundant tropical nature – rather than guarding against it – and emergent aesthetic constitutions of an avowedly "post-colonial" politics. It goes on to demonstrate how the fluid spatialities, and historical and cultural narrativisations of de Silva's work have been drawn into hegemonic articulations of Sinhala Buddhist nationalism in the last few decades, despite her more secular modernist intentions. The paper argues for a situated geopolitical understanding of de Silva's pathbreaking tropical modern architecture.